Odpowiedź :
a) 2x ^-xy ^ - 5x^+2xy ^ =- 3 x^ + xy^
- 3 x^ + xy^= - 3*(1/3)^ + 1/3 * 9^= - 3 * 1/9 + 1/3 * 81 = -1/3 + 27 = 26 i 23
b)
-1/2x do trzeciej y-2/3xy+1/2x do trzeciej y-1/3=
-1/8{x^3}y -2/3xy +1/8{x^3}y -1/3= -2/3xy -1/3 = -2/3*(1/3)*9-1/3= -2/9*9-1/3=
-2-1/3=-2 1/3
Oznaczenie:
{x^3}-------->oznacza x do potęgi trzeciej
a)
-3x²+xy²
-3*(1/3)²+1/3*9²=
-3*1/9+1/3*81=
-1/3+27=
26 2/3
b)
-2/3xy-1/3
-2/3*1/3*9-1/3=
6/3-1/3=
5/3
-3x²+xy²
-3*(1/3)²+1/3*9²=
-3*1/9+1/3*81=
-1/3+27=
26 2/3
b)
-2/3xy-1/3
-2/3*1/3*9-1/3=
6/3-1/3=
5/3